2010
DOI: 10.1016/j.neuroimage.2010.01.049
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala integrates emotional expression and gaze direction in response to dynamic facial expressions

Abstract: Neuroimaging studies suggest that the amygdala integrates emotional expression and gaze direction, but the findings are inconsistent. We hypothesized that the dynamic facial expressions, which are more salient stimuli than static facial expressions are, would reveal the integration of emotional expression and gaze direction in amygdala activity. To test this hypothesis, we presented dynamic and static facial expressions of anger and happiness looking toward and away from the subject, and we visualized brain ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 54 publications
7
68
1
Order By: Relevance
“…We confirm that activity within motorrelated cortical areas arises 150 -200 ms after the onset of a perceived action (Nishitani and Hari, 2002;Caetano et al, 2007;Tkach et al, 2007;Catmur et al, 2010) and that the interaction between gaze direction and emotion takes place at ϳ200 -300 ms (Klucharev and Sams, 2004;Rigato et al, 2010). However, in contrast to recent accounts of human amygdala function in social cue integration (Sander et al, 2007;NЈDiaye et al, 2009;Cristinzio et al, 2010;Sato et al, 2010), we found that emotional content is processed earlier within the amygdala and independently of other cues.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…We confirm that activity within motorrelated cortical areas arises 150 -200 ms after the onset of a perceived action (Nishitani and Hari, 2002;Caetano et al, 2007;Tkach et al, 2007;Catmur et al, 2010) and that the interaction between gaze direction and emotion takes place at ϳ200 -300 ms (Klucharev and Sams, 2004;Rigato et al, 2010). However, in contrast to recent accounts of human amygdala function in social cue integration (Sander et al, 2007;NЈDiaye et al, 2009;Cristinzio et al, 2010;Sato et al, 2010), we found that emotional content is processed earlier within the amygdala and independently of other cues.…”
Section: Discussionsupporting
confidence: 78%
“…Amygdala damage diminishes the brain's response to threatening faces at both the ϳ100 -150 and ϳ500 -600 ms time ranges (Rotshtein et al, 2010), and, in both infants and adults, the interaction between gaze direction and emotion takes place at ϳ200 -300 ms (Klucharev and Sams, 2004;Rigato et al, 2010). Furthermore, previous fMRI studies manipulating self-involvement during face perception revealed that facial expression and gaze direction are integrated in the medial temporal poles (Schilbach et al, 2006;Conty and Grèzes, 2012) or in amygdala (Adams and Kleck, 2003;Hadjikhani et al, 2008;NЈDiaye et al, 2009;Sato et al, 2010). Here, we show that the binding of emotion with gaze direction and pointing gesture arises at ϳ200 ms in the PM.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations